Fresh Osteochondral and Chondral Allograft Preservation and Storage Media: A Systematic Review of the Literature. Issue 6 (May 2022) - Tabbaa, Suzanne M.; Guilak, Farshid; Sah, Robert L.; Bugbee, William D.
Background: Storage procedures and parameters have a significant influence on the health of fresh osteochondral allograft (OCA) cartilage. To date, there is a lack of agreement on the optimal storage conditions for OCAs. Purpose: To systematically review the literature on (1) experimental designs and reporting of key variables of ex vivo (laboratory) studies, (2) the effects of various storage solutions and conditions on cartilage health ex vivo, and (3) in vivo animal studies and human clinical studies evaluating the effect of fresh OCA storage on osteochondral repair and outcomes. Study Design: Systematic review; Level of evidence, 5. Methods: A systematic review was performed using the PubMed, Embase, and Cochrane databases. The inclusion criteria were laboratory studies (ex vivo) reporting cartilage health outcomes after prolonged storage (>3 days) of fresh osteochondral or chondral tissue explants and animal studies (in vivo) reporting outcomes of fresh OCA. The inclusion criteria for clinical studies were studies (>5 patients) that analyzed the relationship of storage time or chondrocyte viability at time of implantation to patient outcomes. Frozen, cryopreserved, decellularized, synthetic, or tissue-engineered grafts were excluded. Results: A total of 55 peer-reviewed articles met the inclusion criteria. Ex vivo studies reported a spectrum of tissue sources and storage solutions and conditions, although the majority of studies lacked complete reporting of key variables, including storage solution formula and environmental conditions. The effect of various conditions (eg, temperature) and storage solutions on cartilage health were inconsistent. Although 60% of animal models suggest that storage time may influence outcomes and 80% indicate inferior outcomes with frozen OCA as compared with fresh OCA, 75% of clinical studies report no correlation between storage time and outcomes. Conclusion: Given the variability in experimental designs and lack of reporting across studies, it is still not possible to determine optimal storage conditions, although animal studies suggest that storage time and chondrocyte viability influence osteochondral repair outcomes. A list of recommendations was developed to encourage reporting of key variables, such as media formulation, environmental factors, and methodologies used. High-quality clinical data are needed to investigate the effects of storage and graft health on outcomes.